Mercury transport and methylmercury production in the lower Cedar River (Iowa) floodplain - Graham, Andrew M.; Van Helten, Seth; Wadle, Austin; Mamrak, Emily; Morsch, Jacob; Lopez, Samuel; Smith, Katherine (Frontiers in Environmental Chemistry, 2023)
Scant attention has been paid to cycling of total mercury (THg) and methylmercury (MeHg) in agriculturally intensive watersheds. Monitoring of Hg and MeHg in river basins provides valuable information on the efficacy of environmental policy and the impacts of land use and climate change on Hg fluxes and biogeochemistry. We report on Hg and MeHg yields in the Cedar River (Iowa), a major tributary of the Upper Mississippi River, and on Hg biogeochemistry in a floodplain of the lower Cedar River, with emphasis on Hg cycling in groundwater and wetland ponds. For the period 2016 to 2018, total Hg yields for the 21,000 km 2 Cedar River watershed ranged from 2.6 to 6.9 µg m -2 yr -1 , or 25 to 70% of estimated wet deposition, and MeHg yields ranged from 0.09 to 0.18 µg m -2 yr -1 . High watershed transfer efficiencies for THg are driven by soil erosion and suspended sediment delivery. Policies and land management practices targeting soil conservation are thus likely to have significant impacts on downstream transport of Hg.Within alluvial groundwaters, Hg and MeHg concentrations were highly spatiotemporally variable, ranging from 0.5 to 2.0 ng/L for THg and 0.03 to 1.50 ng/L for MeHg. Microtopography exerted strong control on groundwater geochemistry and Hg biogeochemical cycling, with groundwater sampled from lower lying swales exhibiting less dissolved oxygen (DO), higher conductivity, higher dissolved organic carbon (DOC), and higher THg and MeHg. The alluvial aquifer exhibits high hydrologic connectivity with the river and groundwater THg and MeHg concentrations responded rapidly to hydrologic events, with MeHg concentrations increasing with a rising water table. Concentrations of THg and MeHg in wetland ponds were elevated compared to groundwater and most strongly correlated with DOC and UV-absorbance. Methylation potentials in pond sediments were among the highest reported for freshwater sediments, up to 0.15 d -1 , which we hypothesize to be linked to high primary productivity associated with nutrient enrichment. Floodplain groundwaters and wetlands constitute important ecosystem control points for downstream MeHg delivery, the magnitude of which is sensitive to changing hydroclimate, especially flood frequency.